Identify Consumer Brand Affinity During Point of Purchase Using SEM to Aid Business Growth - Francis, Santhosh (Digital Repository of Theses, 2025)
This research is being executed to understand how the consumer perspective of brand equity based on the success achieved through top-of-mind presence and resulting in business profitability. The important question is: What are the key drivers to a particular Brand‘s success and failure and how it can be course corrected to achieve the desired outcome by tweaking a particular under-performing driver without any bias. The method involved in identifying the key drivers to enhance Brand equity is called Structural Equation Modeling (SEM).